2016
DOI: 10.1590/s1980-65742016000100001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of endothelial function by flow-mediated dilation in diabetic patients: Effects of physical exercise

Abstract: Abstract--The endothelium is now recognized as an endocrine organ that acts to maintain vascular homeostasis regulating the vascular tone and structure. The endothelial cells synthetize a variety of mediators among them, the main agent is the nitric oxide (NO), a potent vasodilator. NO exerts its protective role preventing leukocyte adhesion and migration, expression of adhesion molecules, platelet aggregation, cell proliferation, and promoting the relaxation of smooth muscle cells. On the other hand, endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
0
3
0
2
Order By: Relevance
“…[ 10 ] T2D is associated with reduced flow-mediated dilatation (FMD), [ 11 ] a noninvasive approach for the assessment of endothelial function. [ 12 , 13 ] However, its impairment suggests an imbalanced production of vasodilators, hence endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] T2D is associated with reduced flow-mediated dilatation (FMD), [ 11 ] a noninvasive approach for the assessment of endothelial function. [ 12 , 13 ] However, its impairment suggests an imbalanced production of vasodilators, hence endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed as percentage change of the arterial diameter from the baseline diameter [8]. FMD has been used in both clinical research and clinical practice [9], and it has been shown to be strongly predictive of future CV events in patients with diabetes mellitus (DM) [10]. Moreover, two previous studies have demonstrated impaired FMD in patients with endstage renal disease [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A Diabetes Mellitus é a ausência de insulina ou inaptidão da insulina de exercer corretamente sua função, tem como característica a hiperglicemia crônica e mudanças no metabolismo dos carboidratos proteínas e lipídeos, uma hiperglicemia prolongada é bastante nociva ao organismo, pois pode desenvolver lesões orgânicas irreversíveis causando danos aos rins, aos olhos, aos nervos, aos pequenos e grandes vasos, danos teciduais, perda de função e falência de vários órgãos (JARRETE; ZANESCO; DELBIN, 2016;SÁ;NAVAS;ALVES, 2014).…”
Section: Introductionunclassified